Resenha de: FORTUNATO MALLIMACI (ED.). RELIGIÓN Y POLÍTICA: PERSPECTIVAS DESDE AMÉRICA LATINA Y EUROPA - de Souza, Bruno Silva (Debates do NER, 2010)
Resenha de: FORTUNATO MALLIMACI (ED.). RELIGIÓN Y POLÍTICA: PERSPECTIVAS DESDE AMÉRICA LATINA Y EUROPA